Elevated Circulating Interleukin-27 in Patients with Coronary Artery Disease Is Associated with Dendritic Cells, Oxidized Low-Density Lipoprotein, and Severity of Coronary Artery Stenosis - Wen Jin; Yiqiao Zhao; Wen Yan; Longxing Cao; Weiwei Zhang; Ming Wang; Ting Zhang; Qiang Fu; Zhiliang Li (Mediators of Inflammation)
Coronary artery disease (CAD) is an immune-mediated chronic inflammatory disease mainly caused by atherosclerosis. The aims of this study were to investigate the role of interleukin-27 (IL-27) in patients with CAD and the severity of coronary artery lesions, which was evaluated by Gensini score and to investigate the biosynthesis of IL-27 and oxidized low-density lipoprotein (ox-LDL) in vitro using monocyte-derived dendritic cells (DCs). To this aim, plasma levels of IL-27, ox-LDL, and Gensini score were analyzed in patients with CAD (n=136) and normal subjects (controls, n=29). IL-27 concentration of the supernatant and the mRNA expression levels of p28 and ebi3, subunits of IL-27, from cultured immature DCs incubated with different concentrations of ox-LDL for 24 h were also analyzed. We found that circulating IL-27 levels were significantly elevated in patients with CAD than in controls (P<0.01), and positively correlated to ox-LDL and Gensini score. ox-LDL dose-dependently upregulated expression of both IL-27 protein and IL-27 (p28 and EBI3) mRNA in vitro, indicating that ox-LDL can stimulate DCs to produce IL-27. These results demonstrate that IL-27 might regulate the network of immunity and inflammation in the pathogenesis of atherosclerosis.